Polyamide 66 microspheres metallised with in situ synthesised gold nanoparticles for a catalytic application - Cheval, Nicolas; Gindy, Nabil; Flowkes, Clifford; Fahmi, Amir (Springer, 2012)
A simple concept is proposed to metallise polyamide 66 (PA66) spherulite structures with in situ synthesised gold nanoparticles (Au NPs) using a wet chemical method. This cost-effective approach, applied to produce a PA66/Au NP hybrid material, offers the advantages of controlling the nanoparticle size, the size distribution and the organic- inorganic interactions. These are the key factors that have to be controlled to construct consistent Au nanostructures which are essential for producing the catalytic activities of interest. The hybrid materials obtained are characterised by means of scanning electron microscopy, transmission electron microscopy, attenuated total reflection-Fourier transform infrared spectrometry and X-ray diffraction spectrometry. The results show that PA66 microspheres obtained via the crystallisation process are coated with Au NPs of 13 nm in size. It was found that controlling the metal coordination is the key parameter to template the Au NPs on the spherulite surfaces. The preparation processes and the key factors leading to the formation of PA66 spherulites coated with Au NPs are discussed. Moreover, the efficiency of the coated spherulites as a potential catalyst is proved by demonstrating the reduction of methylene blue via UV-visible spectrometry.